Hubungan Antara Earning Response Coefficient dengan Karakteristik Perusahaan - Sondang Mariani Rajagukguk (Jurnal Akuntansi, 2017)
AbstractThis research is a literature review about the relation between earnings response coefficient (ERC) with firms’ characteristics. Firms’ characteristic is company specific information that differentiate it from other companies, whereas these characteristics are estimated to be correlated with regard to earning response coefficient. Through this study, we will know why the market response differently on good news or bad news. By understanding the reactions of market on earnings, accountant can improve their understanding about how the accounting information will give benefit to the investors. This understanding will direct and help them in preparing the financial information which is valuable. This earnings response coefficient will be used to measure the unexpected return of the market in response to the unexpected parts of the reported earnings of the firms that has issued the securities.Keywords: Earning Response Coefficient (ERC), Firms’ Characteristics